The effect of PTU on Adiponectin levels in hyperthyroid women during early pregnancy - Hussain Sabah Hussain; Ali Abdelhussain Ghazzay (Zien Journals, 2023)
This study aims to find out the effects associated with the use of propylthiouracil for pregnant women with hyperthyroidism on Adiponectin. The current study was conducted on 60 women with hyperthyroidism and 60 women with normal thyroid glands who attended Al-Diwaniyah Teaching Hospital during the period from February 2022 to May 2023, where they were divided into groups according to the time periods of pregnancy. Adipokine were then measured using the enzyme-linked immunosorbent assay (ELISA) which included Adiponectin Results: shows that there was significant increase in Adiponectin levels during the treatment with PTU in comparison with control groups starts from the first month of pregnancy and elevating through the third month until the fifth month were it was the higher concentration of Adiponectin
Keywords: hyperthyroidism; pregnant; PTU; Adiponectin